Brain Vitamin E Deficiency During Development Is Associated With Increased Glutamate Levels and Anxiety in Adult Mice - Catherine M. Desrumaux; Catherine M. Desrumaux; Catherine M. Desrumaux; Catherine M. Desrumaux; Marine Mansuy; Marine Mansuy; Marine Mansuy; Marine Mansuy; Stéphanie Lemaire; Stéphanie Lemaire; Stéphanie Lemaire; Stéphanie Lemaire; et al. (Frontiers in Behavioral Neuroscience, 2018)
Vitamin E, the most important lipophilic radical scavenging antioxidant in vivo, has a pivotal role in brain. In an earlier study, we observed that adult mice with a defect in the gene encoding plasma phospholipid transfer protein (PLTP) display a moderate reduction in cerebral vitamin E levels, and exacerbated anxiety despite normal locomotion and memory functions. Here we sought to determine whether dietary vitamin E supplementation can modulate neurotransmitter levels and alleviate the increased anxiety phenotype of PLTP-deficient (PLTP−/−) mice. To address this question, a vitamin E-enriched diet was used, and two complementary approches were implemented: (i) “early supplementation”: neurotransmitter levels and anxiety were assessed in 6 months old PLTP−/− mice born from vitamin E-supplemented parents; and (ii) “late supplementation”: neurotransmitter levels and anxiety were assessed in 6 months old PLTP−/− mice fed a vitamin E-enriched diet from weaning. Our results show for the first time that an inadequate supply of vitamin E during development, due to moderate maternal vitamin E deficiency, is associated with reduced brain vitamin E levels at birth and irreversible alterations in brain glutamate levels. They also suggest this deficiency is associated with increased anxiety at adulthood. Thus, the present study leads to conclude on the importance of the micronutrient vitamin E during pregnancy.